Triple-hop distance as a valid predictor of lower limb strength and power - Hamilton, R. T.; Shultz, S. J.; Schmitz, R. J.; Perrin, D. H. (Journal of Athletic Training, 2008)
Hop tests are functional tests that reportedly require strength, power, and postural stability to perform. The extent to which a triple-hop distance (THD) test measures each of these characteristics is relatively unknown.